Resilience and its association with hopelessness, depression, loneliness, post-traumatic stress disorder (PTSD) and suicidal ideations and behavior in a cohort in the Nairobi Metropolitan - David M. Ndetei; Victoria Mutiso; Christine Musyimi; Eric Jeremiah; Pascalyne Nyamai; Samuel Walusaka; Veronica Onyango; Kamaldeep Bhui; Daniel Mamah (Cambridge Prisms: Global Mental Health)
Comprehending resilience in the face of mental health issues is important, especially for young people who deal with a variety of psychological pressures. This study aims to investigate the co-occurrence of several mental health conditions and the role of resilience as a potential intervention in youth 14–25 years in the Nairobi metropolitan area. We recruited 1,972 youths. The following self-administered instruments were used: resilience (ARM-R), hopelessness (BHS), depression (BDI, PHQ-9), PTSD (HTQ), loneliness (UCLA Loneliness Scale) and suicidality (C-SSRS). Descriptive statistics, Pearson correlation and hierarchical multiple regression analyses were conducted on the data. The key findings are that depression and hopelessness showed a strong negative association with resilience. PTSD and recent suicidal ideation and behavior showed less negative association with resilience. Building resilience is an important intervention for the conditions reported in our study among the youth. This study contributes novel insights into the intersection of multiple psychological stressors and resilience, paving the way for more targeted, integrative mental health interventions.